Chemical gardens without silica: the formation of pure metal hydroxide tubes1. Issue 65 (21st August 2015) - Batista, Bruno C.; Steinbock, Oliver
<x xml:space="preserve">Abstract</x> We establish a minimal reaction system for the study of hollow precipitation tubes that involves only hydroxide and metal ions.